2019
DOI: 10.1038/s41598-019-41802-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct endophytes are used by diverse plants for adaptation to karst regions

Abstract: The present study aimed at systematically investigating the endophytic communities of dominant plants in the karst ecosystem. Soil and plant materials were collected and after sequencing of the 16 s RNA, the diversity and abundance of the endophytic community structures in leaves were examined. Our results showed that abundant and diverse endogenous bacteria were associated with the leaves of common dominant plants living in the karst ecological environment. Notably, common traits and significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
0
26
1
Order By: Relevance
“…Although there is already some indication that endophytic bacteria actively sense the plant environment and adjust their behavior in response to changing conditions and plant signals, we still are at the very beginning to understand the interplay between plants and endophytes on a molecular level. Given the growing evidence, that the composition of endophytic communities may influence plant phenotypic traits (Li et al ., 2019a), obtaining comprehensive understanding of the selective forces in the plant environment and the mechanisms of adaptation to this environment by endophytes and endophytic communities may open new avenues to optimize plant productivity and performance via modulating the endophytic communities.…”
Section: Microbiota In Different Plant Compartmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is already some indication that endophytic bacteria actively sense the plant environment and adjust their behavior in response to changing conditions and plant signals, we still are at the very beginning to understand the interplay between plants and endophytes on a molecular level. Given the growing evidence, that the composition of endophytic communities may influence plant phenotypic traits (Li et al ., 2019a), obtaining comprehensive understanding of the selective forces in the plant environment and the mechanisms of adaptation to this environment by endophytes and endophytic communities may open new avenues to optimize plant productivity and performance via modulating the endophytic communities.…”
Section: Microbiota In Different Plant Compartmentsmentioning
confidence: 99%
“…Rapid adaptation of endophytes may be a pre‐requisite for the plant holobiont to better adapt to stress conditions. Many studies have shown that plants growing in unfavorable conditions like hot, drought, saline, and heavy metal contaminated environments can develop different adaptation capacities to stresses, which is partially due to their associated microorganisms (Vandenkoornhuyse et al ., 2015; Li et al ., 2019a). As discussed above, endophytes need to show a number of characteristics to colonize plants internally such as motility and chemotaxis functions or degradation of reactive oxygen species.…”
Section: Improving the Performance Of Endophytes In Promoting Plant Growth And Healthmentioning
confidence: 99%
“…Soils of the cultivated areas were slightly acidic (approximately pH 6.7), and the magnesium and sodium content were higher than that of the wild areas. Li et al (2018 , 2019) suggested that the calcium content in karst regions is a major factor for endophytic bacterial community composition, which in turn helps the plants to adapt to the environment. Soil properties, such as pH, carbon-to-nitrogen ratio, available phosphorous, and potassium also determine the root microbial community directly or via plant growth ( Lauber et al, 2009 ; Bulgarelli et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The properties of soil also affected the root morphology and root exudation ( Neumann et al, 2014 ), which are crucial factors for surrounding bacterial community. The changes of plant physiology modulated the endophytes and soil biological activities ( Jones et al, 2009 ; Li et al, 2018 , 2019 ). Therefore, properties of the calcareous soil might restrict the growth of sensitive plants and can also influence the composition of distinctive bacterial microbiota that may contribute to the adaptation of DPF plants to the karst ecological environment.…”
Section: Discussionmentioning
confidence: 99%
“…endophyte, leaf surface sterilization, Pinus contorta, Populus fremontii, scanning electron microscopy (SEM) Plant endophytes are described as microorganisms living inside plant tissues without deteriorating their hosts' health [1][2][3]. In recent years, studies of plant-endophyte interactions have gained considerable attention due to the potential contributions of these interactions to improve plant health [4][5][6][7][8][9]. However, several methodological obstacles arise when studying endophytes, including the complete removal of leaf surface microorganisms (i.e., leaf epiphytes).…”
Section: Introductionmentioning
confidence: 99%